Stress and Insomnia among Elderly Living in a Nursing Home: A Cross-sectional study - Raufuddin, Raufuddin; Widoyanti, Virki; Wilujeng, Sri (Fundamental and Management Nursing Journal, 2023)
Introduction: Globally, It was estimated that one in three adults experienced insomnia. In Indonesia, 10% or equal to 28 million of the population was reported this particular sleep problem.    Physical illness, environment, drugs used, and stress were reported as the major cause of insomnia. This study aims to analyse the relationship between stress and the incidence of insomnia among elderly living in a nursing, Surabaya, Indonesia. Method: This study applied cross-sectional approach with correlation descriptive design. Population in this study was older adults living in a nursing home. A total of 51 participant recruited through a random simple sampling was involved. The independent variable was stress and dependent was insomnia. A self-report questionnaire was used to collect data from the study participants. Data was statistically test by Contingency Coefficient. Results: There is no relationship between stress and the incidence of insomnia in the elderly (p=0.267). Insomnia might relate to others factors that not explored in the study. Conclusions: The current study highlights insomnia among elderly  is not related to stress events. Even insomnia was a common, nurses need to identify other factors that can contribute to insomnia experienced by the elderly. Thus, further study examines insomnia among elderly is warranty.